Evaluation of date palm fruits quality under different irrigation water salinity levels compared to the fruit available in the market - Hammami, Zied; Mahmoudi, Henda; Al Janaahi, Amna; Singh, Rakesh Kumar (Frontiers in Sustainable Food Systems, 2024)
Introduction The date palm (Phoenix dactylifera L.) is a major component of the agro-food systems of the arid regions. Since it is an indigenous tree, it is an integral part of the local cultural heritage and social and economic life. Date palm cultivation in the region is challenging due to various factors such as water scarcity and soil and water salinity. Methods This research study was conducted to evaluate the quality of commonly sold date palm varieties in the UAE market and grown using saline water at the ICBA research station in Dubai. The study involved measuring physical parameters like fruit weight, size, dimensions, color, volume, Brix, protein, sucrose, glucose, fructose, sugars, phenols, sodium, and potassium, as well as analyzing how consumers perceive the fruit’s quality attributes produced under varying salinity levels. The study evaluated Tamar dates’ texture, flavor, aroma, taste, color, and appearance using a five-point scale from very poor to excellent. Results and discussion The study found that fruit quality is affected by salinity, and there is a significant interaction between variety and salinity treatments. Salinity affects date palm traits, but low to moderate levels do not affect fruit quality. Khalas, Sukkari, and Ajwa-Tul-Madinah are the least affected varieties. High salinity negatively impacts some varieties, leading to decreased fruit quality. However, it is also worth noting that salinity stress can increase the sugar concentration in fruit for specific varieties, as demonstrated in this study on fruit sugar content under such conditions. Among the tested dates, Sukkari from the market, Ajwa-Tul-Madinah irrigated with 5 and 10 dS m−1 have the highest sugar content and many other desirable characteristics. Hierarchical k-means clustering reveals that each genotype performs better under a specific level of salinity, allowing for targeted selection of genotypes for salinity mitigation. Sugar content is crucial in assessing date fruits irrigated with saline water. It should be included in the evaluation criteria to promote the use of saline water for date palm irrigation and save freshwater resources. The study provides valuable insights into different date palm varieties’ behavior under varying salinity levels, enabling farmers to optimize production and establish new evaluation criteria.